A Rare Case Report of Intramedullary Spinal Cord Metastasis (ISCM) from A Known Prostatic Primary - Tamhane, Tejas M; Kachewar, Sushil G; Lakhkar, Dilip L (Nepal Journal of Neuroscience, 2016)
Intramedullary Spinal Cord Metastases (ISCM) is rare as they represent 8.5% of all central nervous system metastases and account for 5% of all intramedullary lesions. Lung cancer is the most common primary malignancy which causes spinal mets followed by other malignancies like Breast, Lymphoma, Leukemia, Malignant Melanoma etc. Only two cases of ISCM from Prostatic primary were reported in the literature previously. Our case represents one such rare occurrence, hence, reported here. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 112-115